The making and unmaking of demand for dairy and chicken in Norway: a systems of provision perspective - Marius Korsnes; Martin Loeng (Sustainability: Science, Practice, & Policy)
This study examines the supply and demand for chicken meat and fresh cow’s milk in Norway and argues that understanding demand as being co-constituted and interrelated with supply is crucial for reducing consumption. This study takes a constructivist systems of provision perspective to examine the chain of activities that links production and consumption. Analyzing how the use of chicken meat and fresh cow’s milk has evolved through socially and historically contingent processes in Norway, the article describes how these products became commonplace through state involvement, nutritional advice, companies, and consumers. The demand for liquid milk decreased in the 1980s, providing a rare insight into a system of provision in decline, although both government and industry actors wanted the situation to be otherwise. This study highlights that the milk-provision system failed to address the factors that contributed to the decline in milk consumption, which worsened the situation for dairy farmers. This is contrasted with the case of chickens, which represents a story of expanded demand through industrial intensification and new food norms. Under the presumption that a theory that explains an increase in demand must also be able to explain a decrease in demand, the analysis highlights the factors that caused a reduction in fresh milk consumption and the factors that led to growth in the demand for chicken meat. The article concludes that a constructivist perspective allows for a more nuanced understanding of the making and unmaking of demand through processes of alignment/misalignment with established political, economic, and societal goals.